Sucrose transporters and sucrose uptake mechanisms in sugarcane - Titus, Charlene H. A. (Charlene Helecyn Agatha) (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc)--University of Stellenbosch, 2004.